Factors influencing development of financial derivatives markets: a survey of listed companies in Kenya - Matumo, Gabriel; Kimani, Maina E.; Ngugi, Nahashon (My University, 2013)
The Kenyan economy is becoming more and more open with international trading constantly increasing and as a result Kenyan firms become moreexposed to foreign exchange rate fluctuations. The relative price changes affect the firms’ competitive market position, leading to changes in cash flows and ultimately, in firms value. While it was observed that firms use a variety of instruments to manage financial risks, it was not clear whether the full potential of these instruments is being realized since not all firms use derivatives and notall firms use all types and more important, whether they are used appropriately. The study found out that the use of financial derivatives instruments by quoted companies in Kenya is mainly influenced by legal and regulatory framework, market environment, operational efficiency and the role offinancial market intermediaries. Hence the study concluded that there is need of building upon existing financial derivatives instruments so as to enhance efficiency and effectiveness in their use in Kenya as modern tools for financial risk management.
Keywords: Derivatives market; counterparty-risks; Systematic risks; Unsystematic risks; emerging markets; hedging